Chlorogenic acid attenuates tet (X)-mediated doxycycline resistance of Riemerella anatipestifer - Han, Yuwen; Li, Min; Su, Dehai; Xiong, Shiyu; Feng, Youshu; Deng, Qin; Ding, Huanzhong (Frontiers in Veterinary Science, 2024)
The increasing resistance of R. anatipestifer has posed a significant threat to the poultry industry in recent years. The tet gene is the primary determinant of tetracycline resistance in numerous bacteria, and the enzyme modification gene tet(X) is predominantly detected in tetracycline-resistant R. anatipestifer strains. In this study, we evaluated the susceptibility of both the standard strain and clinical isolates of R. anatipestifer to doxycycline. The results revealed that the minimum inhibitory concentration of doxycycline for the standard strain was 0.25µg/mL, whereas it exceeded 8µg/mL for the clinical isolates. Furthermore, there was a significant upregulation observed in expression levels of tet(X), tet(A), and tet(O) genes among induced strains. To assess drug susceptibility, shuttle plasmids were constructed to transfer the tet(X) gene into the standard strain of R.anatipestifer followed by treatment with chlorogenic acid. Interestingly, when transferring the tet(X) gene into the standard strain, its sensitivity to doxycycline decreased; however, MIC values for chlorogenic acid remained consistent between both standard and drug-resistant strains of R.anatipestifer. Moreover, we made a surprising discovery that screening passage with chlorogenic acid resulted in increased sensitivity of R.anatipestifer to doxycycline. Further analysis demonstrated a reversal in expression trends among three differentially expressed genes within induced drug resistance group after intervention with chlorogenic acid. The main objective behind this study is to investigate both killing effect exerted by chlorogenic acid on drug-resistant R.anatipestifer as well as its regulatory impact on drug resistance genes. This will provide novel insights and theoretical basis towards development of chlorogenic acid as a promising drug for treatment and control of drug resistance in R.anatipestifer.